2013
DOI: 10.1159/000356259
|View full text |Cite
|
Sign up to set email alerts
|

Massive Abdominoscrotal Hydrocele

Abstract: Abdominoscrotal hydrocele (ASH) is a very rare clinical finding. It is characterized by a large scrotal hydrocele in communication with the abdominal cavity through the inguinal canal. Most reports of ASH have been in the pediatric population. We present the case of a 67-year-old man, with severe liver disease, who was discovered to have massive bilateral ASH secondary to ascites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…ASH was first described by Dupuytren as ‘hydrocele en bissac’ in 1834 [ 2 ]. Bickle defined the phenomenon as an ASH in 1919 [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ASH was first described by Dupuytren as ‘hydrocele en bissac’ in 1834 [ 2 ]. Bickle defined the phenomenon as an ASH in 1919 [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been proposed that as the radius of the fluid collection secreted by the tunica vaginalis increases, the inward pressure decreases, according to LaPlace’s law. This allows the collection to distend above the deep inguinal ring, and develop into the abdominal component of the hydrocele [ 2 ]. It has therefore been suggested that ASH be more accurately described as ‘scrotal-inguinoabdominal’ hydrocele [ 1 ], but we favour scrotal-inguino-retroperitoneal (SIR) hydrocele.…”
Section: Discussionmentioning
confidence: 99%